Pengaruh Model Pembelajaran Collaborative Learning Terhadap Hasil Belajar PAK Siswa Kelas VIII SMP Negeri 4 Siborongborong Tahun Pembelajaran 2023/2024 - Siska Oktavia Sianturi; Damayanti Nababan; Sandy Ariawan (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The research aims to determine the influence of the collaborative learning model on the learning outcomes of PAK class VIII students at SMP Negeri 4 Siborongborong for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the collaborative learning learning model on the PAK learning outcomes of class VIII students at SMP Negeri 4 Siborongborong for the 2023/2024 academic year. Descriptive quantitative research method. The population of all class VIII students at SMP Negeri 4 Siborongborong for the 2023/2024 academic year who are Protestant Christians is 166 people. The sample was taken using purposive sampling, namely 36 students in class VIII-B. The research instrument is a closed questionnaire. The results of the analysis requirements obtained a value of rxy=0.569>rtabel=0.329 and tcount=2.728>ttable=2.042 showing that there is a relationship between the collaborative learning learning model and the PAK learning outcomes of class VIII students at SMP Negeri 4 Siborongborong for the 2023/2024 academic year. From the regression test, the regression equation is obtained. The determination test revealed that the magnitude of the effect was 32.38%. Hypothesis testing obtained Fcount=15.599>Ftable=2.01, so H0 is rejected and Ha is accepted, namely that there is a positive and significant influence between the collaborative learning learning model on the PAK learning outcomes of class VIII students at SMP Negeri 4 Siborongborong for the 2023/2024 academic year.